Effect of Fresh or Cryopreserved Pollen on Seed Setting of Intervarietal and Interspecific Crosses of Gladiolus - Poon, Tul Bahadur; Rao, TM; Rajshekharan, PE; Aswath, C; Kumar, DP (Nepal Journal of Science and Technology, 2013)
An experiment was conducted in the field of Indian Institute of Hortricultural Research, Hessaraghatta, Bangalore during August 2006 to June 2008. The experiment consisting of eight treatment combinations were laid out in ‘2x4’ factorial RCBD with 5 replications to assess seed set per capsule. The results revealed that highly significant differences were observed for number of well-developed seeds and underdeveloped seeds. Among four cross combinations ‘H.S. 88-10-22 x Shobha’ (27.63 well-developed seeds per capsule) and ‘H.S. 84-7-11 x Shobha’ (27.01 well-developed seeds per capsule) were significantly higher than those of other two cross combinations. The interaction effect of fresh pollen- cum- ‘H.S.88-10-22 x Shobha’ produced significantly higher number of welldeveloped seeds (41.02 per capsule) than those of the other treatment combinations. In contrast, treatment combinations viz., cryopreserved pollen- cum- ‘H.S. 88-10-22 x Shobha’ produced the lowest number of welldeveloped seeds (10.85 per capsule).Inclusion of fresh pollen to genotype ‘Shobha’ and cryopreserved pollen of H.S. 88-10-22' revealed better performances for maximum seed set per capsule. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 31-34 DOI: http://dx.doi.org/10.3126/njst.v14i1.8874